The first exon of region E1a genes of adenoviruses 5 and 12 encodes a separate functional protein domain. - Jochemsen, A G (1984)
The transforming E1 regions of human adenoviruses Ad5 and Ad12 differ from each other in the frequency by which they can transform primary baby rat kidney cells, and in their ability to modulate expression of class I major histocompatibility (MHC) genes. We have investigated whether these two properties, which are determined by region E1a, can be assigned to one of the two protein segments encoded by the E1a exons. To that end, we have constructed chimaeric E1a regions, in which the 5' E1a exon of Ad5 was linked to the 3' E1a exon of Ad12, and vice versa. It was found that, although there is only a limited degree of homology between Ad5 and Ad12 E1a (approximately 40% at the protein level), the hybrid E1a products are functional in transformation. Furthermore, both the frequency of transformation and the modulation of class I MHC gene expression appeared to be determined by the first E1a exon. These results indicate that the first E1a exon encodes a separate functional domain in the E1a proteins.